The role of primary α grains in the degree of transformation texture obeying the Burgers orientation relationship in Zr alloys. (September 2022) - Cao, Yucheng; Wu, Tianxian; Xia, Liang; Feng, Pengfei; Jiang, Chao; Chen, Ding
Abstract: The microstructure and texture evolution of Zr-xNb-0.4Mo (x = 0, 0.2, 0.4, 0.6 and 1.0 wt%) alloys are characterized using scanning electron microscopy (SEM), transmission electron microscope (TEM) and electron backscatter diffraction (EBSD) technique. The aim is to elucidate the role of primary α grains in the degree of transformation texture obeying the Burgers orientation relationship (OR) in Zr alloys. The primary α grain is produced by adjusting Nb content in Zr alloys. The crystallographic orientations of Zr-xNb-0.4Mo alloys show that the degree of transformation texture obeying the Burgers OR increases with the proportion of primary α grains decreasing. Until no primary α grains exist, the transformation texture obeys the Burgers OR strictly. The primary α grains can exert great influence on variant selection by restricting the growth of high-temperature β grains and acting as nucleation sites. The fact that primary α grains are the origins of variant selection is observed. Meanwhile, variant selection occurs in both the duplex microstructure and full martensite plates during the water-quenching process. The texture weakening of the duplex microstructure is attributed to the new texture components given by martensite plates. In terms of microstructure, a series of precipitates, Zr3 (Nb, Mo, Fe), are found in a primary α grain. Highlights: The degree of transformation texture obeying the Burgers OR is studied. The result shows that primary α grains are the origins of variant selection. Texture weakening is attributed to the new components given by martensite. Some precipitates, Zr3 (Nb, Mo, Fe), were found in the primary α grains.